REMAJA SEHAT DENGAN GIZI SEIMBANG: STRATEGI EDUKASI NUTRISI YANG EFEKTIF - Yoselina, Prima; Anggita, Kheniva Diah; Marni, Linda; Armaita, Armaita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Balanced nutrition education in adolescents is a preventive effort to overcome various diseases related to unhealthy diets. Adolescents need optimal nutrition that can improve their health and activity because adolescents are still in a stage of rapid growth and development. According to the results of the 2023 Indonesian Health Survey data, the number of adolescents aged 13-15 years who are overweight has increased to 16.2% where previously 16% in 2018, while adolescents aged 13-15 years who are obese by 11.2% in 2018 increased to 12.1% in 2023. The purpose of this community service is to provide education to increase adolescents' knowledge about balanced nutrition, foods that can and should not be eaten, and healthy lifestyles. The method used in the implementation of this community service is to provide counseling through interactive lectures by providing leaflets containing balanced nutrition materials to adolescents at SMPN 4 VII Koto Sungai Sarik, Padang Pariaman Regency. The target of this activity is 25 students in grade VII. Students can participate in activities from the beginning to the end of the activity and an evaluation is carried out at the end of the activity. Students are enthusiastic about the activities carried out and it is hoped that students can apply the knowledge they have gained and share information with friends and others so that teenagers can live healthy and can live well. Keywords: education;balanced nutrition;adolescents.